Muscle Biopsy and Electromyography Correlation - Naddaf, Elie; Milone, Margherita; Mauermann, Michelle L.; Mandrekar, Jayawant; Litchy, William J. (Frontiers in Neurology, 2018)
INTRODUCTION: In myopathies, the correlation of individual electromyographic and histopathologic findings remains poorly explored, as most previous studies have focused on the ability of muscle biopsy and electromyography to distinguish the neuropathic versus myopathic nature of the underlying neuromuscular disease. METHODS: We identified 100 patients who had a muscle biopsy and electromyography performed on identical muscles. We used a detailed grading system ranging from 0- normal to 4- severe; and graded 16 histopathologic findings in each biopsy. Electromyography findings were also graded from 0 to 4 according to the standard protocol in our EMG laboratory. We used Kendall’s tau for non-parametric ordinal correlation analysis. RESULTS: Fibrillation potentials correlated with atrophic, necrotic and regenerating fibers, fibers harboring vacuoles, fiber splitting, fibers reacting for non-specific esterase, fibers with congophilic inclusions, inflammation (endoymysial and perimysial), and increased endomysial connective tissue. Short-duration motor unit potentials correlated with atrophic, necrotic and regenerating fibers, increased endomysial connective tissue, and perimysial inflammation. Long-duration motor unit potentials correlated with fiber-type grouping. Increased phases of motor unit potentials correlated with atrophic fibers, increased endomysial connective tissue, and fibers reacting for non-specific esterase; while increased turns correlated with atrophic and regenerating fibers, increased endomysial connective tissue and target formations. Rapid recruitment correlated with regenerating fibers, perimysial inflammation and increased endomysial connective tissue. DISCUSSION: By demonstrating a clear correlation of various electromyographic and histopathologic findings, this study improves interpreting electrodiagnostic testing in myopathies, and serves as the basis to further assess the correlation between clinical, electromyographic and histopathologic findings.